Characterization of piezocrystals for practical configurations with temperature- and pressure-dependent electrical impedance spectroscopy - Qiu, Zhen (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2011)
Piezoelectric single crystal materials such as (x)Pb(Mg(1/3)Nb(2/3))O(3-)(1-x)PbTiO(3) (PMN-PT) have, by some measures, significantly better performance than established piezoelectric ceramics for ultrasound applications. However, they are also subject to phase transitions affecting their behavior at temperatures and pressures encountered in underwater sonar and actuator applications and in non-destructive testing at elevated temperatures. Materials with modified compositions to reduce these problems are now under development, but application-oriented characterization techniques need further attention. Characterization with temperature variation has been reported extensively, but the range of parameters measured is often limited and the effects of pressure variation have received almost no attention. Furthermore, variation in properties between samples is now rarely reported. The focus of this paper is an experimental system set up with commercially available equipment and software to carry out characterization of piezoelectric single crystals with variation in temperature, pressure, and electrical bias fields found in typical practical use. We illustrate its use with data from bulk thickness-mode PMN-29%PT samples, demonstrating variation among nominally identical samples and showing not only the commonly reported changes in permittivity with temperature for bulk material but also significant and complicated changes with pressure and bias field and additional ultrasonic modes which are attributed to material phase changes. The insight this provides may allow the transducer engineer to accelerate new material adoption in devices